Students' views and experiences of the training and use of phonetic transcription in speech and language therapy: the Irish perspective - Yanushevskaya, Irena (My University, 2021)
Phonetic transcription is an essential skill for a practising speech and language therapist (SLT) required during the assessment, diagnosis and management of clients with speech difficulties. It is vital that appropriate training is received by student SLTs to ensure that they carry out phonetic transcription accurately and reliably once out in the workplace. This study investigates the views and experiences of final year SLT students regarding the training in phonetic transcription they received in university, with the aim to identify what poses difficulties for them and what could be done to enhance their learning. Responses from 40 participants representing one cohort of SLT students, graduates of a particular year, were collected using an online questionnaire. The majority of the respondents consider phonetic transcription an important professional skill and plan on maintaining it after graduating. Learning phonetic transcription was easy/quite easy for 57% of the respondents; however, the confidence in transcription skills was rather low: 70% of them reported not being confident and fully equipped to enter the workforce with their transcription skills. The main difficulties were associated with narrow (impressionistic) transcription and transcription of disordered speech. 58% of the respondents found the teaching environment suitable; however, a recurring theme is the need for small-group tutorials during which the lecturers could provide feedback to individual students more efficiently. Participants' responses suggest that more clinically relevant transcription practice of disordered speech, the opportunity to refresh and apply phonetic transcription skills throughout the four-year curriculum and smaller group teaching would benefit their learning and enhance their confidence using transcription on placements and in the workforce.
PUBLISHED
Keywords: Phonetic transcription; SLT-in-training; Phonetic training; Student perspective; Phonetic transcription; Phonetics; speech and language therapy